2014
DOI: 10.5271/sjweh.3467
|View full text |Cite
|
Sign up to set email alerts
|

How compatible are participatory ergonomics programs with occupational health and safety management systems?

Abstract: Prevention of musculoskeletal disorders (MSD) often involves a participatory rrgonomics (PE) program. The paper compares the PE approach with occupational health and safety management system (OHSMS). The PE literature did not speak to many elements of OHSMS. It is expected that paying attention to management system frameworks could make prevention of MSD activities more effective and sustainable.Affiliation:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…Some papers (Fernández-Muñiz et al, 2012a;Santos et al, 2013) reported and stressed out the benefits collected from OHSMS implementation, the perceptions and attitudes from certified OHSMS companies regarding safety behaviour and its effectiveness (Robson et al, 2007;Chen and Li, 2012). Other papers focused on the assessment of the OHSMS (Abad et al, 2013;Inan et al, 2017), on the performance of the OHSMS (Azadeh et al, 2012.;Desa et al, 2013b;Lo et al, 2014), on the comparison between the OHSAS 18001 and national standards (Abidin and Irniza, 2015), between certified and non-certified companies concerning safety climate (Ghahramani, 2016) and point out and promote linkages between the OHSMS implementation with other constructs or aspects such as sustainability (Marhani et al, 2013;Qi et al, 2013), voluntary safety management (Paas et al, 2015), safety behaviour (Fernández-Muñiz et al, 2012b), participatory ergonomics (Yazdani et al, 2015), psychosocial risks (Jespersen et al, 2016), safety management (Vinodkumar and Bhasi, 2011), organizational learning (Granerud and Rocha, 2011;Silva et al, 2017) and decision making aiming at effectiveness improvement (Mohammadfam et al, 2016). Some recent published papers address the OHSMS in an International Journal of Occupational and Environmental Safety, 1:1 (2017) 11-28 13 integrated context and other dissect some pertinent and relevant IT issues aiming at a successful management of the system of systems.…”
Section: Certifiable Occupational Health and Safety Management Systemsmentioning
confidence: 99%
“…Some papers (Fernández-Muñiz et al, 2012a;Santos et al, 2013) reported and stressed out the benefits collected from OHSMS implementation, the perceptions and attitudes from certified OHSMS companies regarding safety behaviour and its effectiveness (Robson et al, 2007;Chen and Li, 2012). Other papers focused on the assessment of the OHSMS (Abad et al, 2013;Inan et al, 2017), on the performance of the OHSMS (Azadeh et al, 2012.;Desa et al, 2013b;Lo et al, 2014), on the comparison between the OHSAS 18001 and national standards (Abidin and Irniza, 2015), between certified and non-certified companies concerning safety climate (Ghahramani, 2016) and point out and promote linkages between the OHSMS implementation with other constructs or aspects such as sustainability (Marhani et al, 2013;Qi et al, 2013), voluntary safety management (Paas et al, 2015), safety behaviour (Fernández-Muñiz et al, 2012b), participatory ergonomics (Yazdani et al, 2015), psychosocial risks (Jespersen et al, 2016), safety management (Vinodkumar and Bhasi, 2011), organizational learning (Granerud and Rocha, 2011;Silva et al, 2017) and decision making aiming at effectiveness improvement (Mohammadfam et al, 2016). Some recent published papers address the OHSMS in an International Journal of Occupational and Environmental Safety, 1:1 (2017) 11-28 13 integrated context and other dissect some pertinent and relevant IT issues aiming at a successful management of the system of systems.…”
Section: Certifiable Occupational Health and Safety Management Systemsmentioning
confidence: 99%
“…Whether a decision about changes in the work environment is efficient, and its expected net benefits are great, depends on whether the information from relevant studies is complete. However, most studies in occupational health sciences are focused partially on the psychosocial work environment [5,28,29], the ergonomic work conditions [6,30,31], and the physical characteristics of the workplace [7,8,32], while the socioeconomic impacts of the work environment have not been given enough attention. One-dimensional studies of the work environment impair not only the improvement of occupational health and labour productivity, but also the estimation of the economic results and thus the valuation of such studies.…”
Section: Comprehensive View Of the Work Environmentmentioning
confidence: 99%
“…Participative Ergonomics (PE) practices are commonly presented as a desirable approach for the prevention of MSD (Noro and Imada, 1991). Ergonomic programs for the prevention of MSD vary in complexity, but most of those reported in the literature appear to be set up in isolation from management system frameworks (Yazdani et al, 2015). This isolation was perhaps first conceived to highlight the work-relatedness of MSD and to increase the awareness that these disorders are as important as acute injuries.…”
Section: Introductionmentioning
confidence: 98%